2011
DOI: 10.1136/jnnp-2011-300828
|View full text |Cite
|
Sign up to set email alerts
|

Grey matter atrophy in cognitively impaired Parkinson's disease

Abstract: Marked grey matter atrophy occurs in PD with dementia but far less extensive changes are evident in PD-MCI. Some grey matter atrophy precedes the development of dementia but may be accelerated once frank dementia begins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
172
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(204 citation statements)
references
References 42 publications
(64 reference statements)
28
172
2
2
Order By: Relevance
“…Varying degrees of atrophy have been reported in patients with PD without dementia, [41][42][43] with mixed evidence of an association between atrophy and neuropsychological measures. 44 Within a cohort of 90 patients with mild PD without dementia, we investigated SDGM volumes and cortical thickness and examined their associations with cognitive functioning and disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Varying degrees of atrophy have been reported in patients with PD without dementia, [41][42][43] with mixed evidence of an association between atrophy and neuropsychological measures. 44 Within a cohort of 90 patients with mild PD without dementia, we investigated SDGM volumes and cortical thickness and examined their associations with cognitive functioning and disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Parkinson's disease (PD) with dementia (PDD) is characterized by reduced gray matter volume in allocortical and neocortical regions including parietal and frontal cortices, cingulate gyrus (CG), and in temporal lobe regions such as the hippocampus and amygdala [1]. Histologically, a complex synucleinopathy is present comprising Lewy bodies (LB), Lewy neurites (LN), and Lewy grains (LG) [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The general consensus suggests widespread cortical atrophy in PDD, although it is less severe compared to AD and DLB (Beyer, Larsen, & Aarsland, 2007;Burton, McKeith, Burn, Williams, & O'Brien, 2004). Cortical atrophy progresses linearly across the cognitive stages in PD and affects temporal, frontal, parietal (Beyer et al, 2007;Burton et al, 2004;Melzer et al, 2012;Pagonabarraga et al, 2013;Tam, Burton, McKeith, Burn, & O'Brien, 2005;Weintraub et al, 2011;Zarei et al, 2013), and less commonly, occipital regions (Burton et al, 2004). Subcortical GM changes can also occur in PDD and affect mainly the hippocampus (Apostolova et al, 2010;Camicioli et al, 2003;Junque et al, 2005;Zarei et al, 2013), thalamus (Burton et al, 2004), putamen (Burton et al, 2004), amygdala (Junque et al, 2005;Zarei et al, 2013), and the caudate (Apostolova et al, 2010;Burton et al, 2004).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Subcortical GM changes can also occur in PDD and affect mainly the hippocampus (Apostolova et al, 2010;Camicioli et al, 2003;Junque et al, 2005;Zarei et al, 2013), thalamus (Burton et al, 2004), putamen (Burton et al, 2004), amygdala (Junque et al, 2005;Zarei et al, 2013), and the caudate (Apostolova et al, 2010;Burton et al, 2004). Regional atrophy in temporal, parietal, and frontal cortices (Melzer et al, 2012;Pagonabarraga et al, 2013;Pereira et al, 2014;Segura et al, 2014;Weintraub et al, 2011) and thalamus (Mak, Bergsland, Dwyer, Zivadinov, & Kandiah, 2014) and hippocampus (Weintraub et al, 2011) has been observed in PD-MCI.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%